The color of things in Henry James's The Ambassadors: complicating the process of vision. Issue 2 (3rd April 2018) - Géracht, Maurice A.
Abstract: This article focuses on how description generally, and color particularly, "bear upon" Henry James's The Ambassadors (1903), the action of which is understood as the process and education of Lambert Strether's vision and that of the reader. While the narrative of The Ambassadors is largely Strether's "intimate adventure" and "even the projection of his consciousness upon it, " he is not at "once hero and historian" (XXI, xvi), a distinction too often erased. Focusing on the use of color in The Ambassadors helps bring this distinction into relief, both on Strether's sense of past and present, of "should" and "is, " and on the very separate narrator/historian's perspective. The central intelligence separately shapes the education and process of Strether's vision, as well as that of the reader.